Acanthocepola abbreviata (Valenciennes, 1835), a rare bandfish: morphological description and new distribution record for Malaysia - Arshad, A (2015)
Acanthocepola abbreviata is a rare fish from Family Cepolidae, Order Perciformers. Its distribution has been recorded in the open South China Sea at depths of 20-200 m and for the first time recorded in the seagrass bed of Tg. Adang Laut shoal at shallow depth of 2.3 m in the Tebrau Strait, Johor. The taxonomic aspects and morphological descriptions are given in detail since this species is poorly described previously.